Psychometric properties of the translated Spanish version of the Pain Self-Efficacy Questionnaire - Perez-Dominguez, Borja; Perpiña-Martinez, Sara; Escobio-Prieto, Isabel; de la Fuente-Costa, Marta; Rodriguez-Rodriguez, Alvaro Manuel; Blanco-Diaz, Maria (Frontiers in Medicine, 2023)
Introduction Some patients with rotator cuff injuries do not report significant changes in pain-related outcomes. Pain self-efficacy, which is commonly assessed using the Pain Self-Efficacy Questionnaire, may contribute toward this outcome. However, a Spanish adaptation of this questionnaire is currently lacking. Therefore, this study’s purpose was developing the Spanish version of this questionnaire, and assess its psychometric properties. Methods The Spanish version of the Pain Self-Efficacy Questionnaire was translated and culturally adapted, and a sample of 107 patients with rotator cuff injuries completed the questionnaire to examine its convergent validity (analyzing its correlation with the Tampa Scale of Kinesiophobia), its test–retest reliability, for which a subset of 40 participants completed again the questionnaire, and its internal consistency. Results Translation was conducted without any problems, and 107 participants completed the study. Mean scores for the Pain Self-Efficacy Questionnaire were 45.2 points (standard deviation, 11.4). The Pain Self-Efficacy Questionnaire showed a moderate negative correlation with the Tampa Scale of Kinesiophobia (Pearson’s correlation index r = −0.48) supporting its convergent validity. High test–retest reliability (Intraclass Correlation Coefficient of 0.90) and excellent internal consistency (Cronbach’s α value of 0.92) were also found. Discussion The Spanish version of the Pain Self-Efficacy Questionnaire presents high validity, test–retest reliability, and internal consistency to assess pain self-efficacy in patients suffering rotator cuff injuries in Spanish-speaking settings.